Avaliação da ação de antibiótico natural na fermentação alcoólica contaminada por cultura mista - Leite, Inácio Ramos (2011)
Brazilian ethanol is attracting the attention of the world as a renewable energy source and economically viable. Brazil has in its favor some fundamental issues such as climate, area and technology, able to make this biofuel becomes a pillar of the national and international markets for renewable fuels. So, faced with such potential, realized the importance of using byproducts as a source of income in order to increase sources of revenue in the sector. Numerous studies have been performed so they can assess the best conditions for the application of Saccharomyces cerevisiae as a source of nutrients in the human diet and of several herds. However, contamination control of these processes is largely based on the use of chemical antibiotics, and residues left by these products in yeast became a problem after being banned in several countries, the use of these strains in human food and animals. There is a need to develop other mechanisms to control the damage caused by bacterial contamination during the production of ethanol without residue in yeast. Given this situation, the objective of this thesis was to evaluate the performance of the natural antibiotic BETABIO 45 extracted from the hops in the disinfection of contaminated alcoholic fermentations with mixed cultures. For this, we tried to optimize the initial concentrations of inoculum, bacterial contaminants and natural antibiotic, employing central composite design and response surface technique. From the above mentioned technique was selected as the best condition for the application of natural antibiotic studied the dosage of 20 mg/L in fermentations conducted in cell concentration in the order of 108 cells/mL and contamination of 104 CFU/mL. In addition, we compared the action of natural antibiotic to one of the most widespread chemical antibiotics in distilleries, the KAMORAN. The natural antibiotic BETABIO 45 showed very similar performance to the antibiotic KAMORAN. However, this was more effective in fighting bacteria. Applied at the beginning of fermentations contaminated, the action of antibiotics could not prevent the income were affected, but both showed strong bactericidal effect on the mixed culture of bacteria in the fermentation media used. The natural product made with the percentage reduction of bacteria was always above 90% and in some cases, reductions reach percentages above 99% throughout the fermentation process. This paper presents further fermentation kinetics of uncontaminated and contaminated with and without the use of natural antibiotic extracted from hops.